A Bibliometric Analysis of Intention to Leave in TheManufacturing Industries - Muliawan, Indra (West Science Business and Management, 2025)
Intention to leave is a serious challenge faced by companies, especially in the manufacturing sector which demands high efficiency and sustained productivity. High levels of employee exit intentions can have a direct impact on operational stability, increased recruitment costs, and disruption of work team performance. This study aims to analyze the factors that influence employee quit intentions in the manufacturing industry. By using a qualitative approach, this research is expected to provide a deeper understanding of the dynamics, experiences and underlying causes behind the intention to leave. The findings of this study are expected to serve as a basis for consideration for human resource managers and practitioners in formulating effective retention policies and creating a work environment that supports workforce sustainability in the manufacturing sector.